HUBUNGAN DURASI BERMAIN GADGED (GAME EDUKASI) DENGAN TINGKAT PERKEMBANGAN ANAK USIA 4-6 TAHUN DI TK DAHLIA DARMAJI - Beti Haerani; Lalu Wiresanta; Baiq Larasati Septami (LPPM STIKES Muhammadiyah Kendal, 2019)
The development of gadgeds (educational game) is very rapid, giving an impact on children’s development level because children who often play gadged (educational game) will experience retardment at his development level. The aim of the study to determine the relations beetween Relationship Duration Playing Gadged (educational game) With Children’s Development Level Aged 4-6 Years Old At Kindergarten School of Dahlia Darmaji. Cross sectional research design. The population were 51 kindergaeden children of Dahlia Darmaji aged 4-6 years old. Sample were 45 respondents with total sampling method. The independet variable was relationship duration playing gadged (educational game) and the dependent variable was the children’s development level aged 4-6 years old. It measured by questionnaire and children DDST. Data analysis technique used chi-square test α=0,05. The results showed that duration of playing gadged (educational game) often were 21 respondent (46,7%), and children’s development level aged 4-6 years old late were 34 respondent (75,6%). Chi-square test results α=0,05 obtained p=0,000 < 0,05 so H1 was accepted, it meant there was relationship duration of playing gadged (educational game) with children’s development level aged 4-6 years old. It is expected that parents can limit children in the duration of playing gadged (educational game) and oversee the activities carried out on children while playing gadged.